Culture, academy and society (Encuentros, 2022)
As guest editor, PhD. Juan Manuel Barceló-Sánchez describes and synthesises the texts presented in this issue of the journal Encuentros. In volume 20-01, he highlights the focus on drawing eleven social, cultural and educational challenges through the eyes of the researcher, in his attempt to better understand the changing world we inhabit.
Keywords: Liquid society; pandemic; Covid-19; Teleworking; Education; Mass Media Communication; Educational innovation; Reviews; Dance; Ethnography